The ones that are wanted : communication and the politics of representation in a photographic exhibition - Kratz, Corinne Ann, 1953- (University of California Press, 2002)
The Okiek people of Kenya's forested highlands have a long history of hunting, honey gathering, and trading with their Maasai and Kipsigis neighbors; several decades ago, they also began farming and herding. This book follows a traveling exhibition of anthropologist Corinne Kratz's photographs of the Okiek through showings at seven venues, including the National Museum in Nairobi and the Smithsonian Institution in Washington, D.C. Kratz tells the story of the exhibition--the stereotypes it sought to challenge, how commentaries by Okiek people were incorporated, and different ways that viewers.